2017
DOI: 10.12669/pjms.333.12554
|View full text |Cite
|
Sign up to set email alerts
|

Values of procalcitonin and C-reactive proteins in the diagnosis and treatment of chronic obstructive pulmonary disease having concomitant bacterial infection

Abstract: Objective:To observe the changes in the levels of C-reactive protein (CRP) and procalcitonin (PCT) in serum of patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) and to compare with the values of CRP in combination with PCT in the diagnosis and treatment of infective exacerbation of COPD.Methods:One hundred and sixty-four patients who developed acute exacerbation of COPD and admitted to the Binzhou People’s Hospital from March 2014 to December 2015 were selected. They were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“… 39 Levels of CRP in combination with PCT is a reliable index for determining the existence of bacterial infection in AECOPD patients. 40 A study by Marras showed that higher CRP levels could predict exacerbation in COPD. 41 High serum PCT levels (OR= 2.0, 95% CI: 1.2–3.2, P= 0.006) and CRP levels (OR = 1.2, 95% CI: 1.1–1.3, P<0.001) could predicted NIMV failure for patients with AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Levels of CRP in combination with PCT is a reliable index for determining the existence of bacterial infection in AECOPD patients. 40 A study by Marras showed that higher CRP levels could predict exacerbation in COPD. 41 High serum PCT levels (OR= 2.0, 95% CI: 1.2–3.2, P= 0.006) and CRP levels (OR = 1.2, 95% CI: 1.1–1.3, P<0.001) could predicted NIMV failure for patients with AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of PCT, CRP and SAA have important clinical significance in the diagnosis and treatment of Sepsis and other infectious diseases. 5 - 10 …”
Section: Discussionmentioning
confidence: 99%
“…The levels of PCT, CRP and SAA have important clinical significance in the diagnosis and treatment of Sepsis and other infectious diseases. [5][6][7][8][9][10] Application value of PCT, hs-CRP and SAA detection SAA is one of the markers of inflammatory activity in the acute response phase, mainly produced by macrophages. 11 SAA has the characteristics of a low basal level and high induced expression, and it is produced in large quantities in the inflammatory acute response period.…”
Section: Discussionmentioning
confidence: 99%
“…В одном из недавно проведенных исследований [33] было показано, что в группе с инфекционным обострени-ем ХОБЛ повышение ПКТ составляло 2,52 ± 2,89 нг/мл, а уровень СРБ 73,81 ± 18,27 мг/мл, тогда как в группе с неинфекционным обострением заболевания, не требую-щего приема антибиотика, уровень ПКТ и СРБ составил 0,17 ± 0,07 нг/мл 7,91 ± 3,01 мг/л соответственно.…”
Section: пациенты с хб/хобл переносят от 1 до 4 и более обострений в unclassified